2019
DOI: 10.2166/wp.2019.164
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the Ganges Water Sharing arrangement

Abstract: The 1996 Ganges Water Sharing Treaty was an important breakthrough in solving disputes over sharing Ganges water between India and Bangladesh. This study evaluates cooperation reflected in the Treaty by performing a quantitative analysis on available water sharing data. The study recognized that inaccurate projection of future flow and the obligation of allocating guaranteed 991 m3/s flows perpetuate the ongoing water sharing conflicts. The provision of guaranteed minimal flow alternately to India and Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…Trans-boundary river represents a hydro-geographic unit which is divided by static national or international political boundaries ( Rahman et al, 2019 ). The importance of trans-boundary rivers is always high due to their international significance in social, cultural, economic, political, ecological and physical aspects.…”
Section: Methodsmentioning
confidence: 99%
“…Trans-boundary river represents a hydro-geographic unit which is divided by static national or international political boundaries ( Rahman et al, 2019 ). The importance of trans-boundary rivers is always high due to their international significance in social, cultural, economic, political, ecological and physical aspects.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, no clear evidence for the 10‐day cycle of water releases was detected. Similarly high flows also occurred in 2014, and even at that time no 10 day cycle in water sharing was detected (Rahman et al, 2019). Water sharing and regulation were expected to intensify during the period with the lowest flow (11 March to 31 May), when both countries are guaranteed to receive a minimum quantum of water in alternating 10 day periods (Government of India & Government of Bangladesh, 1996; Penny et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…The India-Bangladesh treaty implementation has reportedly increased average dry season water flows towards Bangladesh by releases of more water in the Ganga during the 10 day allocation periods (Penny et al, 2020). Estimated water availability at Farakka in the study period was found to be consistently greater than the average value of 3,000 m 3 s À1 (Thomas, 2017;Rahman et al, 2019), which was also backed up by local reports, and probably related to the anomalous and intensive flooding in 2019 (Bhatt et al, 2020). As a result, no clear evidence for the 10-day cycle of water releases was detected.…”
Section: Impacts On Hydrologymentioning
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, Bangladesh argues that they do not receive their fair share of water allocated for them in the non-monsoon. Rahman et al (2019) indicated that the treaty underestimated the impact of climate variability and possibly increased upstream water abstraction creating obligations for guaranteed flows perpetuating the risk of water-sharing conflicts. On the other hand, India and Nepal signed the Kosi agreement in 1954 to construct a barrage between the India-Nepal border to regulate the flow of the river, flood management, power generation, and irrigation purposes.…”
Section: Changes In Surface Water Flows and Challengesmentioning
confidence: 99%